Being Flesh: Bodies, History and LLF. Issue 1 (1st January 2023) - King, Helen
Abstract : Like history, the body played a disappointingly minor role in the Living in Love and Faith ( LLF ) outputs. This article introduces the relationship between medical theories of the body and theological understandings of a God who became flesh. History shows us many times at which the appeal of binaries has dominated understandings of our enfleshed existence, but also the range of other ways in which bodies have been understood. Using as examples the roles of blood and milk in readings of Mary and of Eve, it illustrates the ways in which fleshly people have experienced and understood a faith in which flesh plays a central role, and concludes that the richness of the changing past is one reason why LLF preferred not to explore it.